Ferulic Acid Combined With Bone Marrow Mesenchymal Stem Cells Attenuates the Activation of Hepatic Stellate Cells and Alleviates Liver Fibrosis - Zhang, Rui; Li, Wenhang; Jiang, Xiaodan; Cui, Xinyi; You, Hongjie; Tang, Zuoqing; Liu, Wenlan (Frontiers in Pharmacology, 2022)
Bone marrow mesenchymal stem cells (BMSCs) can effectively alleviate liver fibrosis, but the efficacy of cell therapy alone is insufficient. In recent years, a combination of traditional Chinese medicine (TCM) and cell therapy has been increasingly used to treat diseases in clinical trials. Ferulic acid (FA) is highly effective in treating liver fibrosis, and a combination of cells and drugs is being tested in clinical trials. Therefore, we combined BMSCs and Ferulic acid to treat CCl4-induced fibrosis and determine whether this combination was more effective than single treatment. We used BMSCs and FA to treat CCl4-induced fibrosis in rat models, observed their therapeutic effects, and investigated the specific mechanism of this combination therapy in liver fibrosis. We created a BMSC/hepatic stellate cell (HSC) coculture system and used FA to treat activated HSCs to verify the specific mechanism. Then, we used cytochalasin D and angiotensin II to investigate whether BMSCs and FA inactivate HSCs through cytoskeletal rearrangement. MiR-19b-3p was enriched in BMSCs and targeted TGF-β receptor II (TGF-βR2). We separately transfected miR-19b-3p into HSCs and BMSCs and detected hepatic stellate cell activation. We found that the expression of the profibrotic markers α-SMA and COL1-A1 was significantly decreased in the combination group of rats. α-SMA and COL1-A1 levels were also significantly decreased in the HSCs with the combination treatment. Cytoskeletal rearrangement of HSCs was inhibited in the combination group, and RhoA/ROCK pathway gene expression was decreased. Following angiotensin II treatment, COL1-A1 and α-SMA expression increased, while with cytochalasin D treatment, profibrotic gene expression decreased in HSCs. The expression of COL1-A1, α-SMA and RhoA/ROCK pathway genes was decreased in the activated HSCs treated with a miR-19b-3p mimic, indicating that miR-19b-3p inactivated HSCs by suppressing RhoA/ROCK signalling. In contrast, profibrotic gene expression was significantly decreased in the BMSCs treated with the miR-19b-3p mimic and FA or a miR-19b-3p inhibitor and FA compared with the BMSCs treated with the miR-19b-3p mimic alone. In conclusion, the combination therapy had better effects than FA or BMSCs alone. BMSC and FA treatment attenuated HSC activation and liver fibrosis by inhibiting cytoskeletal rearrangement and delivering miR-19b-3p to activated HSCs, inactivating RhoA/ROCK signalling. FA-based combination therapy showed better inhibitory effects on HSC activation.